STUDYING THE HEALING PROPERTIES OF ALOE PLANT - Turdiyeva Odinaxon Mamirovna; Qaxxorova Fotimaxon Komiljonovna (Galaxy International Interdisciplinary Research Journal, 2023)
Aloe vera, a juicy plant born in arid areas, has been used for centuries for its healing properties. Famous for its therapeutic advantages, this paper focuses on reviewing and discussing scientific evidence supporting the various medicinal properties of aloe vegetation. Aloe vera shows promising wound healing, anti-inflammatory, immunomodulated, antioxidant, anti-microbial and anti-cancer properties. This extensive review of the available research provides an in-depth study of the application of aloe plant and its components in modern medicine.